Óleos essenciais no controle de células planctônicas e sésseis de Staphylococcus aureus - Souza, Tenille Ribeiro de (2015)
Sthapylococcus aureus is a Gram positive bacteria, pathogenic in foods, capable of producing enterotoxins and are often involved in food outbreaks. Biofilms form on biotic and abiotic surfaces, which are constant source of contamination and need to be controlled. The aim of this study was to evaluate the antimicrobial activity of essential oils (EOs) of Cinnamomum cassia, Cinnamomum camphora, Litsea cubeba, Origanum vulgare, Rosmarinus officinalis, Thymus vulgaris and Syzygium aromaticum on planktonic cells and sessile of Staphylococcus aureus ATCC 5674 and Staphylococcus aureus 8702 and to evaluate the effect of the combination of these EOs on the biofilm formed by these two strains of stainless steel AISI 304, with the substrate UHT skimmed milk. To evaluate the antimicrobial activity of the EOs, determined to MIC (minimum inhibitory concentration) and MBC (minimum bactericidal concentration) of EOs tested on planktonic cells and determined the MBCb (minimum bactericidal concentration on the biofilm). The two strains of S. aureus showed different resistances tested EO, with the ATCC 8702 strain more resistant than the EOATCC 5674. Among the evaluated EOs, the EOs of C. cassia were selected, C. camphora, L. cubeba for antimicrobial evaluation of sessile cells. These EOs were selected based on lowest MBC, 0.3125% of C. cassia, C. camphora 1.25% and 0.63% of L. cubeba about ATCC 5674, and these EOs also had the lowest concentrations of ATCC 8702, except for EO C. camphora (MBC 5%). When EOs C. cassia, L. cubeb C. camphor and sessile cells were tested against S. aureus, the two strains showed different behavior evaluated, and when biofilm ATCC 5674 was more resistant than EOs when tested planktonic state. Sanitizing solutions based on the combination of EO sC. cassia, L. cubeb and C. camphora were evaluated for biofilm formed by ATCC 5674 and ATCC 8702 in UHT skimmed milk after 72h of incubation. Also tested was one sanitizing solution based on a combination of EOsC. cassia, L. cubeba and C. camphor in combination with enzymatic detergent. The sanitizing solutions based on the evaluated were able to reduce EOs 2.5 log CFU / cm 2 on both strains tested, obtaining significant results (p <0.05) compared to control. The sanitizing solution containing the EOs and the enzymatic detergent was not significantly different from other treatments. The combination of the EO showed promising results as sanitizers for use in the food industries.